Pharmacokinetics and metabolic disposition of a potent and selective kynurenine monooxygenase inhibitor, CHDI-340246, in laboratory animals. (3rd October 2021) - Khetarpal, Vinod; Herbst, Todd; Shefchek, Diana; Ash, Steven; Fitzsimmons, Michael; Gohdes, Mark; Munoz-Sanjuan, Ignacio; Dominguez, Celia
Abstract: The disposition of a novel kynurenine monooxygenase inhibitor, CHDI-340246, was investigated in vitro and in animals. In vitro, there was minimal metabolic turnover of CHDI-340246 in all species. The protein binding was higher in human plasma (99.7%) relative to other species. In all species, blood clearance was low (<20% of liver blood flow) and volume of distribution was small (<0.5 L/kg). The terminal half-life was longer in monkeys (9 hr) than in mice, rats, or dogs (1–2 hr). CHDI-340246 was orally bioavailable (>60%) in all species. In rats, [ 14 C]CHDI-340246 showed wide distribution of radioactivity in all tissues except brain and testes. In rats, the parent drug was the major circulating moiety with minor amounts of a sulphate conjugate of an O -dealkylated metabolite. The elimination occurred via the urinary route and to a lesser extent by biliary route, but mostly as metabolites. In cynomolgus monkeys, the parent drug predominated in plasma with only trace amounts of metabolites detected. Acyl glucuronide conjugate of CHDI-340246 was not detected in plasma of rats or monkeys. Overall, the ADME profile of CHDI-340246 was favourable in rats and monkeys for potential evaluation of KMO inhibition in humans.